The Dialogue between Islam and the West: Challenges and Strategies for Coexistence - Klaina, Mekki (Darul Yasin Al Sys, 2025)
Coexistence among nations and peoples cannot be achieved in a context of isolation and avoidance of dialogue with others, whether at the individual, group, institutional, or state level. Dialogue helps to bridge perspectives and remove misunderstandings. While some speak of a